2015
DOI: 10.1155/2015/478375
|View full text |Cite
|
Sign up to set email alerts
|

Gallium Nitride Electrical Characteristics Extraction and Uniformity Sorting

Abstract: This study examined the output electrical characteristics—current-voltage (I-V) output, threshold voltage, and parasitic capacitance—of novel gallium nitride (GaN) power transistors. Experimental measurements revealed that both enhanced- and depletion-mode GaN field-effect transistors (FETs) containing different components of identical specifications yielded varied turn-off impedance; hence, the FET quality was inconsistent. Establishing standardized electrical measurements can provide necessary information fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Results from other studies [11] have revealed that the lower the V S(off) values are, the closer the parasitic capacitances are to those specified on the datasheet, with the devices with the lowest V S(off) being used as test transistors. Here, the off-state voltage V s(off) of the fabricated cascode GaN FET was 20 V, and the leakage current obtained using the curve tracer and the calculated leakage current were extremely close (20 V/3.64 MΩ = 5.5 µA).…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Results from other studies [11] have revealed that the lower the V S(off) values are, the closer the parasitic capacitances are to those specified on the datasheet, with the devices with the lowest V S(off) being used as test transistors. Here, the off-state voltage V s(off) of the fabricated cascode GaN FET was 20 V, and the leakage current obtained using the curve tracer and the calculated leakage current were extremely close (20 V/3.64 MΩ = 5.5 µA).…”
Section: Discussionmentioning
confidence: 96%
“…Figure 12 shows the results of the analysis of the leakage current that was obtained using the curve tracer. The plot of VDS versus IDSS reveals that the leakage current hold was 2.2 μA when the drain-to-source voltage was higher than 22 V. This leakage current result was approximated from uniformity sorting methods developed elsewhere [11]. VS(off) was measured after applying different drain-to-source voltages between 10 and 180 V (red circles in Figure 11).…”
Section: Switching Performance With the Double-pulse Testermentioning
confidence: 92%
See 3 more Smart Citations